306 - Loneliness and mortality in older adults and the role of depression. (October 2020) - Holwerda, T.J.; Rhebergen, D.; Comijs, H.C.; Dekker, J.J.M.; Stek, M.L.
Abstract : Background: The prevalence of loneliness increases with age. The presence of loneliness in older adults has been found to be associated with health problems such as depression, decreased cognitive functioning, increases in systolic blood pressure and increased mortality. The underlying mechanisms of the higher mortality risk are largely unknown. Methods: Meta-analysis to investigate the present evidence for the associations between loneliness and mortality. Cross-sectional studies investigating the associations between loneliness and cardiovascular disease and between loneliness and cortisol in 378 depressed and 132 non-depressed older adults. Results: Loneliness appears to be associated with increased mortality, although when only studies are included that consider depression as a covariate, the association is not significant. Therefore it seems likely that depression plays a mediating role in the higher mortality risk. We did not find a significant association between loneliness and cardiovascular disease. In contrast, loneliness was significantly associated with lower cortisol output and decreased dexamethasone suppression. Discussion: The results and their implications for prevention and treatment will be discussed from a clinical perspective as well as a general health perspective. Is loneliness as potentially dangerous as depression?